Open Access Medical Repositories: Status and Development Trends - S. I. Yumasheva (Библиосфера)
The issue of reflecting the scientific achievements of individual scientists and the results of research activities of research teams in the information environment is of great importance for many branches of science and practice, including medicine, where open data can improve the provision of medical care and influence healthcare policy. The effectiveness of search queries and the further effective use of the data obtained in research and practice, especially during epidemics and the treatment of serious diseases, largely depend on accessibility of medical information. Scientific repositories allow the management of all kinds of research results, integration with information systems, and compliance with the FAIR principles. The aim of the study is to identify and analyze development, indexing (in catalogs), visibility by search engines, type-specific characteristics, etc., of open access medical repositories in Russia and abroad. As a result, of the study, the following conclusions are made: 1) the number of repositories in the world is growing, including an increase in their number in the subject area “Medicine and Health”; 2) the infrastructure of Russian open access information platforms is being formed. However, open medical repositories are being developed poorly, most part of which is not represented in global catalogs (OpenDOAR) and is incompatible with the OAI-PMN standard, which allows the collection of data from repositories by various search engines. Thus, the research results are invisible in Internet search results, and Russian medical repositories are not present in the rankings of world repositories.